Managing public health data: taking SDG as an example - Ab Rahman, Jamalludin (Malaysian Public Health Physicians Association, 2016)
Public health generates and uses a lot of data. Data grows exponentially from kilobytes few years back, megabytes, gigabytes now and soon petabytes and exabytes. Accordingly, the information era shifting from PC to internet, or we called now as Web 1.0, then Web 2.0 and now many experts believe that we are in Web 3.0 period where portability and mobile computing are the trend. Public health must adopt and adapt to take its full advantage and to be efficient. Sustainable development goals (SDG) require a lot of data and will generate a lot of data as well. United Nation aware of this need and an independent expert advisory group was established to oversee this matter. This talk will discuss on how they manage this big data.